This child is also mine : a narrative approach to the phenomenon of atypical custodial grandparenthood - Malinauskas, Gedas (Acta Universitatis Lapponiensis, ISSN 0788-7604, 2011)
Abstract.
Keywords: Grandparents as parents; Kinship care; Child Custody; narratiivisuus; kokemukset; isovanhemmuus; sukulaiset; sijaisvanhemmat; isovanhemmat; lapsen huolto; elämäntilanne; työskentely ulkomailla; narratiivinen tutkimus; Liettua